SECOND-DERIVATIVE SPECTROPHOTOMETRY FOR THE ANALYSIS OF SIMVASTATIN IN POLYMERIC NANOCAPSULES - Patrícia Gomes (Drug Analytical Research, 2019)
Conventional spectrophotometry methods are very susceptible to the presence of interferences in complex mixtures such as nanoparticules, requiring prior treatment or extraction of the analyte, and not always providing an adequate response. Derivative spectrophotometry method is capable to eliminate its interference; it is an alternative method for drugs determination in complex matrices. This work investigated the utility of derivate spectrophotometry in assay of simvastatin in polymeric nanocapsules (SIVNC). Shimadzu® UV-1650 double-beam spectrophotometer with 1.0 cm quartz cells was used in this study. The second-order derivative spectrum was obtained employing Δλ=20,000 nm and scaling factor=9.0. The determinations were made at 239 nm (2D239) by zero-crossing method. 2D239 method was validated employing the parameters: specificity, linearity, robustness, precision and accuracy. Results: The specificity test showed there was no interference of constituents commonly found in SIVNC formulation in 2D239. The standard curve showed a correlation coefficient of 0.994. The robustness was evaluated by small changes in the conditions of sample analysis and however, no significant changes were observed regarding drug quantitation. The precision was demonstrated by relative standard deviation (RSD) of intra-day (RSD=1.61-3.76) and inter-day studies (RSD=2.32). The recovery test resulted in an average of 100.66%, which confirmed the accuracy of the method. The procedure was simple and rapid; therefore this technique offers an alternative for determination of SIVNC without interferences.